KONSTRUKSI PARTISIPEL {âING} DAN {âED} SEBAGAI MODIFIKATOR BEBAS DALAM BAHASA INGGRIS - , Bambang Suseno, Prof. Dr. I Dewa Putu Wijana, S.U., M.A. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This research is aimed at analysing âing and âed participial constructions in a number of issues of the daily newspaper The Jakarta Post. The two participial constructions take the form as clauses, and more often than not they may be found attached to independent clauses. Once attached, bothâing and âed participial constructions remain fixed, in spite of the fact that the independent clause to which they are attached may undergo changes. The changes usually concerns its subject or verb, i.e. when the subject which is a singular noun turns to a plural noun, or when the tense of the verb turns from past to present. Although the verb of the independent clause changes, the verb in the clause with {âing} and {âed} participle do not change at all in that it is nonfinite in nature, except that it is paraphrased to become a finite adverbial clause with added elements such as a subordinate conjunction and a pronoun subject, relevant to that in the independent clause.The paraphrase consequently determines the meaning that the clause bears, i.e. whether it refers to time, cause, manner, or result depending on its context. The above-mentioned clauses composed of {âing} and {âed} participles are known as free modifiers. The use of free modifiers brings about effectiveness, particularly in terms of writing. In analysing clauses composed of {âing} and {â ed} participles functioning as free modifiers, the researcher uses a theory put forward by Hornby in terms of verb patterns they may belong to. Besides, he also uses theories put forward by Marius and Wiener, Swan, Frank, and Harp and Klarner, and Quirk et al who share their opinion in line with functions and distributions of positions the clauses may have. The nature of the research is qualitative descriptive, i.e. the researcher makes use of library research and note-taking. The data is then classified according to the types of participles under discussion. Afterwards, the data are analysed using agih method. In the end, the research findings are presented informally written form. It is on the basis of his research upon free modifiers whose constructions are with {âing} and {âed} participles that the researcher finds their three different positions in sentences, namely initial, medial, final. The initial position of the free modifier signifies its modification to the verb. The free modifier in medial position signifies its modification to its antecedent, and that in final position signifies its modification to the subject of the whole sentence.